?LEVELS OF CADMIUM, CHROMIUM AND LEAD IN DUMPSITES SOIL, EARTHWORM (LYBRODRILUS VIOLACEOUS), HOUSEFLY (MUSCA DOMESTICA) AND DRAGON FLY (LIBELLULA LUCTOSA) (Biological Sciences - PJSIR, 2003)
Chemical analyses of cadmium, chromium and lead in dumpsites soil, earthworm (Lybrodrilus violaceous), housefly (Musca domestica) and in indigenous dragonfly (Libellula luctosa) were performed by atomic absorption spectropho- tometry to estimate the degree of metal pollution in two Lagos dumpsites located at Iba Housing Estate (dumpsite A) and Soluos along LASU - Isheri road (dumpsite B). Soil pH and moisture content were also determined. Chromium was not detected (ND) in most of the samples except in the soil samples whose mean and standard deviation (SD) were 0.43 ± 0.37 ?g/g and 0.23 ± 0.37 ?g/g, respectively for dumpsites A and B, and the earthworm samples harvested from dumpsite B (1.00 ± 1.41 ?g/g). The cadmium levels were 4.00 ± 3.16 ?g/g and 7.50 ± 6.37 ?g/g for earthworm; 2.86 ± 1.43 ?g/g and 4.29 ± 3.74 ?g/g for housefly, 0.75 ± 1.26 ?g/g and 1.25 ± 0.95 ?g/g for dragonfly, respectively for dumpsites A and B. However, the concentration of lead in the invertebrates were, 130.00 ± 112.58 ?g/g and 105.75 ± 94.44 ?g/g for earthworm; 145.71 ± 101.87 ?g/g and 225.71± 79.31 ?g/g for housefly; 165.00 ± 69.78 ?g/g and 85.00 ± 69.73 ?g/g for dragonfly respectively for dumpsites A and B. Cadmium and lead levels were found to be higher in the invertebrates harvested from the dumpsites than those collected from the non-dumpsites. The non-dumpsite values for cadmium were 1.24 ± 0.94 ?g/g, 0.45 ± 0.56 ?g/g and 0.38 ± 0.14 ?g/g for earthworm, housefly and dragonfly, respectively. Similarly, the non-dumpsite lead levels for earthworm, housefly and dragonfly were 23.12 ± 10.11 ?g/g, 20.75 ± 11.85 ?g/g and 33.62 ± 14.95 ?g/g, respectively.